Aechmea fasciata Silver Vase - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS, 2017)
This document is about Aechmea fasciata, commonly known as Silver Vase. It details the plant’s characteristics, including its silver-grey, banded foliage and brilliant pink flower stalk. The document covers growth requirements, such as partial shade and well-drained soil, and uses for mass planting, containers, and ground cover. It also highlights propagation methods and potential problems like scale and root rot. The bold form and coarse texture make it ideal for landscape design. Original publication date September 1999.